2020
DOI: 10.5194/soil-6-95-2020
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse monitoring of root water uptake using electrical resistivity tomography and mise-à-la-masse: a vineyard infiltration experiment

Abstract: Abstract. This paper presents a time-lapse application of electrical methods (electrical resistivity tomography, ERT; and mise-à-la-masse, MALM) for monitoring plant roots and their activity (root water uptake) during a controlled infiltration experiment. The use of non-invasive geophysical monitoring is of increasing interest as these techniques provide time-lapse imaging of processes that otherwise can only be measured at few specific spatial locations. The experiment here described was conducted in a vineya… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
(76 reference statements)
1
30
0
Order By: Relevance
“…This study describes the first direct and concurrent characterization of the root-soil current pathway and root architecture. Intrinsic differences in the root electrical properties of maize, cotton, grapevines, and orange trees emerge from the combined interpretation of our results with those presented by Mary et al (2018Mary et al ( , 2019, and Mary et al 2020).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study describes the first direct and concurrent characterization of the root-soil current pathway and root architecture. Intrinsic differences in the root electrical properties of maize, cotton, grapevines, and orange trees emerge from the combined interpretation of our results with those presented by Mary et al (2018Mary et al ( , 2019, and Mary et al 2020).…”
Section: Discussionsupporting
confidence: 85%
“…In their study on field grapevines, Mary et al (2018Mary et al ( , 2019Mary et al ( , 2020 concluded that the CSD could be used to infer the root depth distribution. Because of the significant suberization of major roots in grapevines and orange trees, the electric current could penetrate deep into the root system before significant leakage occured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(soil/field conditions). Mary et al (2020) also highlighted the irrigation influence on the current pathways in the SRS continuum. In light of the newly available evidence, Peruzzo et al (2020) discussed F I G U R E 1 Configuration of the electrodes and electrical impedance spectroscopy (EIS) channels for the (a) field and (b) hoop house acquisitions.…”
Section: Core Ideasmentioning
confidence: 96%
“…For example, Mary et al. (2020) demonstrated that the joint application of electrical resistivity tomography and mise‐a‐la‐masse (MALM) provide information about the extent of active roots of a grapevine, and Peruzzo et al. (2020) show that MALM can also be applied for herbaceous plants.…”
Section: Introductionmentioning
confidence: 99%